The effect of land-use change on river watershed quality (case study: Cimahi Watershed, West Java, Indonesia). Issue 1 (November 2021) - Nurhayati, S A; Marselina, M; Sabar, A
Abstract: Increasing population growth is one of the impacts of the growth of a city or district in an area. This also happened in the Cimahi watershed area. As the population grows, so does the need for land which increases the land-use change in the Cimahi watershed. Land-use changes will affect the surrounding environment and one of them is the river, especially river water quality. As a watershed area, there is one main river that is the source of life as well as the Cimahi watershed, whose main river is the Cimahi River. The purpose of this study was calculated the relationship between land-use change in the Cimahi watershed and the water quality parameters of the Cimahi River. The correlation between the two was calculated using Pearson correlation. Water quality parameters can be seen based on BOD and DO values. BOD and DO values are the opposite because good water quality has high DO values and low BOD values. The correlation between land-use change and BOD was 0.328 is in the area of settlements area. In contrast, to DO values, an increase in settlements/industrial zones will further reduce DO values so that both have a negative correlation, which is indicated by a value of -0, 535. The correlation between settlements with pH and temperature values is 0.664 and 0.812. While the correlation between settlements with TSS and TDS values are 0.333 and 0.529, respectively. In this study, it can be seen that there is a relationship between the decline in water quality and changes in land use.